HUBUNGAN ANTARA SELF-EFFICACY DAN SOCIAL LOAFING PADA SISWA SEKOLAH MENENGAH ATAS - Leony Anastasya Paath; Dewita Karema Sarajar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Unlike most previous studies that have focused primarily on college student populations, this study addresses a gap in the literature by examining the relationship between self-efficacy and social loafing among senior high school students, a group of adolescents with distinct group-work dynamics and collective evaluation patterns. This study aimed to analyze the direction and strength of the relationship between self-efficacy and social loafing in the context of collaborative learning among senior high school students. A quantitative approach with a correlational design was employed. The participants consisted of 388 senior high school students in Indonesia selected through accidental sampling. Data were collected using a self-efficacy scale and a social loafing scale, and were analyzed using Spearman’s correlation because the data were not normally distributed. The results showed a significant, strong, and positive relationship between self-efficacy and social loafing (ρ = 0.642; p < 0.01). This finding indicates that higher levels of students’ self-efficacy are associated with higher reported tendencies of social loafing in group work. This result differs from the initial hypothesis and from several previous findings that generally associate high self-efficacy with active participation. Theoretically, this study demonstrates the contextual limitations of self-efficacy theory in adolescent collaborative learning situations with limited individual accountability. Practically, the findings emphasize the importance of clear role distribution, individual contribution assessment, and accountability mechanisms in group assignments to reduce social loafing among senior high school students. ABSTRAK Berbeda dengan mayoritas penelitian sebelumnya yang lebih banyak berfokus pada populasi mahasiswa, penelitian ini mengisi kesenjangan literatur dengan mengkaji hubungan antara self-efficacy dan social loafing pada siswa Sekolah Menengah Atas (SMA), yaitu kelompok remaja yang memiliki dinamika kerja kelompok dan pola evaluasi kolektif yang berbeda dari mahasiswa. Penelitian ini bertujuan menganalisis arah dan kekuatan hubungan antara self-efficacy dan social loafing dalam konteks pembelajaran kolaboratif siswa SMA. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Partisipan terdiri atas 388 siswa SMA di Indonesia yang dipilih melalui teknik accidental sampling. Data dikumpulkan menggunakan skala self-efficacy dan skala social loafing, kemudian dianalisis dengan korelasi Spearman karena data tidak berdistribusi normal. Hasil penelitian menunjukkan adanya hubungan yang signifikan, kuat, dan positif antara self-efficacy dan social loafing (r = 0,642; p < 0,01). Temuan ini menunjukkan bahwa semakin tinggi self-efficacy siswa, semakin tinggi pula kecenderungan social loafing yang dilaporkan dalam kerja kelompok. Hasil ini berbeda dari hipotesis awal dan sebagian temuan terdahulu yang umumnya mengaitkan self-efficacy tinggi dengan partisipasi aktif. Secara teoretis, penelitian ini menunjukkan batasan kontekstual teori self-efficacy dalam situasi pembelajaran kolaboratif remaja yang minim akuntabilitas individu. Secara praktis, temuan ini menegaskan pentingnya pembagian peran yang jelas, evaluasi kontribusi individu, dan mekanisme akuntabilitas dalam tugas kelompok untuk mengurangi social loafing pada siswa SMA.